Gaya Kepemimpinan Memoderasi Hubungan Komitmen Organisasi Dengan Senjangan Anggaran Dengan Karakteristik Organisasi Sebagai Variabel Anteseden - Vallery Michaelle Felicia; Monika Palupi Murniati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims is to determine factors that can cause budgetary slack. More specifically, the purpose of this study is to find out whether there is a moderating effect between leadership style and organizational commitment and budgetary slack by adding organizational characteristics as the antecedent variable of organizational commitment. The type of research used in this study is quantitative with experimental methods by providing treatment to the subjects involved. The design used for this experiment is a 2x2 design for the variables of leadership style and organizational characteristics. The result of this study is that managers with high organizational characteristics tend to have greater organizational commitment than managers with low organizational characteristics. Meanwhile, leadership style does not moderate the relationship between organizational commitment and budgetary slack. From the results of this study, it can be concluded that hight organizational characteristics can affect a manager’s organizational commitment. Companies need to pay attention to the characteristics of their workers, which in this case means instrumental communication or the quality of information conveyed by managers to their subordinates. Keywords: Budgetary slack; leadership style; organizational commitment; organizational characteristics; instrumental communication.